From policy to practice: lessons from Karnataka about implementation of tobacco control laws - Pragati B Hebbar; Upendra Bhojani; John Kennedy; Vishal Rao (Wolters Kluwer Medknow Publications, 2017)
Background: Tobacco use accounts for eight to nine lakh adult deaths annually in India. India enacted a national legislation "Cigarettes and Other Tobacco Products Act, 2003" (COTPA) to protect health of non-smokers and reduce tobacco consumption. However, even a decade after enacting this law, its implementation remains suboptimal and variable across the Indian states. Karnataka has shown leadership on this front by enacting a state law and implementing COTPA at (sub-) district levels. We, therefore, aim to analyze COTPA implementation processes in Karnataka to understand how COTPA can be effectively implemented. Methods: We developed a case study of COTPA implementation in Karnataka using reports from health, police, education, and transport departments as well as government orders and media reports related to COTPA. We analyzed these data to map and understand the role played by the government agencies in COTPA implementation. We used the proportion of the districts reporting COTPA violations, the number of COTPA violations cases reported, and the proportion of schools reporting compliance with COTPA as proxy measures for COTPA implementation. Results: We found that five government agencies (police, education, health, transport, and urban development) played a major role in COTPA implementation. All the police districts reported COTPA violations with 59,594 cases in a year (April 2013-March 2014). Three of the district anti-tobacco cells and two of the transport divisions reported 1130 and 14,543 cases of COTPA violations, respectively, in the same year. In addition, 84.7% of schools complied with signage requirements of COTPA. COTPA reporting was made part of the reporting systems within health, police, and education departments. The health department created awareness on tobacco harms and COTPA. Conclusions: COTPA implementation in Karnataka was made possible through integrating COTPA implementation within structure/functions of five government agencies.